PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS III SD 3 TENGGELES - Fariza Sauqi Mahmada; F.Shoufika Hilyana; Khamdun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to identify that there is influence and improvement in the Discovery Learning Learning Model on Science Learning Outcomes for class III SD 3 Tenggeles.The problem in this research is motivated by the lack of understanding of students in receiving learning material and the lack of understanding of students in a reading, this is because students' reading literacy is still low. This of course can affect learning outcomes in grade 3 students in science content. This study aims to identify the effect of the discovery learning model assisted by concrete media on the science learning outcomes of third grade students at SD 3 Tenggeles. This research method is a quantitative pre-experimental design. The population of this research were all class III students, totaling 22 students.